Hybrid Passive Control Strategies for Reducing the Displacements at the Base of Seismic Isolated Structures - Di Matteo, Alberto; Masnata, Chiara; Pirrotta, Antonina (Frontiers in Built Environment, 2019)
In this paper, the use of hybrid passive control strategies to mitigate the seismic response of a base-isolated structure is examined. The control performance of three different types of devices used for reducing base displacements of isolated buildings is investigated. Specifically, the Tuned Mass Damper (TMD), the New Tuned Mass Damper (New TMD) and the Tuned Liquid Column Damper (TLCD), each one associated to a Base Isolated structure (BI), have been considered. The seismic induced vibration control of base-isolated structures equipped with the TMD, New TMD or the TLCD is examined and compared with that of the base-isolated system without devices, using real recorded seismic signals as external input. Data show that the New TMD is the most effective in controlling the response of base-isolated structures so that it can be considered as a practical and appealing means to mitigate the dynamic response of base-isolated structures.